Seberapa Teologiskah Teologi Biblika: Relasi antara Teologi Sistematika dan Teologi Biblika - Thio Christian Sulistio (STT Iman Jakarta, 2020)
The relationship between biblical theology and systematic theology has been seen as separate disciplines nowadays. Biblical theology only looking for what the text of the Bible meant for the first reader meanwhile systematic theology only attempts to find the meaning of the Bible text for today's people. Biblical theology is an objective study meanwhile systematic theology is a study based on the religious belief of the theologians. This paper, through literature research, tries to give a proposal that biblical theology and systematic theology has a close relationship. Both come directly from the Bible that they have a parallel and dialogical relationship.AbstrakRelasi teologi sistematika dan teologi biblika pada masa kini dipandang sebagai dua bidang ilmu yang terpisah. Teologi biblika hanya berupaya mencari apa makna teks pada masa penulis Alkitab sedangkan teologi sistematika hanya berpusat pada menyampaikan makna teks pada masa kini. Teologi biblika adalah studi obyektif sedangkan teologi sistematika adalah studi yang berdasar pengakuan iman seseorang. Paper ini, melalui penelitian literatur yang ada, mencoba mengusulkan bahwa teologi biblika dan teologi sistematika memiliki relasi yang erat dimana keduanya berakar dari Alkitab dan bersifat pararel dan dialogis.